1978
DOI: 10.1099/0022-1317-39-2-281
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid Requirement of Adenovirus Multiplication

Abstract: SUMMARYThe absence from the medium of any of the 13 amino acids essential for cell growth has an inhibiting effect on the multiplication of adenovirus 9-I5 and adenovirus I in HeLa cell cultures. The inhibition is accentuated by previous amino acid starvation of the cultures. Whereas with arginine deprivation, the arginine pool inside the cells is at a minimum within 3o rain, the cells are assumed to adapt slowly to the new metabolic state, which is characterized by an increased 'turnover' of protein synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
3

Year Published

1979
1979
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 20 publications
0
23
0
3
Order By: Relevance
“…However, DNA synthesis in Inf B is still active after the peak in viral titer. Similarly, Wigand and Kumel (1978) saw a maximum in DNA production at around 20 h postinfection, which then dropped drastically. Usually DNA is stable and a drop in content may indicate that the cell integrity is affected.…”
Section: Discussionmentioning
confidence: 92%
“…However, DNA synthesis in Inf B is still active after the peak in viral titer. Similarly, Wigand and Kumel (1978) saw a maximum in DNA production at around 20 h postinfection, which then dropped drastically. Usually DNA is stable and a drop in content may indicate that the cell integrity is affected.…”
Section: Discussionmentioning
confidence: 92%
“…The reason why incomplete virions are not assembled subsequent to the release from the arginine block, may be due to the absence of a critical protein required for assembly which is only synthesized during the early portion of the late phase of infection. Indeed recent studies with actinomycin D suggested that such a protein might be translated from an mRNA transcribed before 16 hours postinfection (18).…”
Section: Diseussionmentioning
confidence: 99%
“…Our results confirm the finding that none of the viral polypeptides which are demonstrable by current SI)S-polyacrylamide gel electrophoresis techniques are inhibited by arginine deprivation. Interestingly, viral DNA synthesized during a short period of arginine deficiency is incorporated into virions subsequent to reversal of the arginine block, while such viruses incorporated only newly synthesized proteins eventhough large pools of proteins synthesized during deficiency were available (6,11,18). That amino acid starvation is not the only cause for the non-utilization of 'old' pools of proteins for virus assembly was demonstrated by the non-utilization of such 'old' protein pools when a temperature-sensitive assembly mutant was shifted to the permissive temperature (8).…”
Section: Diseussionmentioning
confidence: 99%
See 2 more Smart Citations